2012
DOI: 10.1126/science.1228172
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Native Influenza Virion Ribonucleoproteins

Abstract: The influenza viruses cause annual epidemics of respiratory disease and occasional pandemics, which constitute a major public-health issue. The segmented negative-stranded RNAs are associated with the polymerase complex and nucleoprotein (NP), forming ribonucleoproteins (RNPs), which are responsible for virus transcription and replication. We describe the structure of native RNPs derived from virions. They show a double-helical conformation in which two NP strands of opposite polarity are associated with each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
297
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 273 publications
(318 citation statements)
references
References 46 publications
14
297
2
Order By: Relevance
“…We observed a varying diameter of the loop at the terminus of the cRNP, with three to seven NP molecules being present within the loop. This observation is consistent with previous reports that the loop end of the vRNP comprises five to eight NP molecules in one study (3) and three NP molecules in another study (2). In contrast to previous studies, which analyzed a mixture of vRNPs corresponding to RNA segments of various lengths, here we analyze one particular cRNP with an RNA segment of a defined length.…”
Section: Discussioncontrasting
confidence: 51%
See 3 more Smart Citations
“…We observed a varying diameter of the loop at the terminus of the cRNP, with three to seven NP molecules being present within the loop. This observation is consistent with previous reports that the loop end of the vRNP comprises five to eight NP molecules in one study (3) and three NP molecules in another study (2). In contrast to previous studies, which analyzed a mixture of vRNPs corresponding to RNA segments of various lengths, here we analyze one particular cRNP with an RNA segment of a defined length.…”
Section: Discussioncontrasting
confidence: 51%
“…Our data revealed that the replicative intermediate of influenza virus exists as an individual structured particle that comprises cRNA, NP, and RdRp. We observed that the cRNP particle contains three major domains, the central filament and two distinct termini, one terminus harboring a loop and the other a structure that we interpret as the RdRp, on the basis of analogy to previously published structures of vRNPs (2,3). The central filament exhibited a helical arrangement, similar to the reported vRNP filament structure (2,3) in which the helical arrangement of the filament is facilitated by NP-NP interactions.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Three structurally dissimilar types of viral helical capsids have been studied so far: capsids of filamentous bacteriophages resembling, in structure and biogenesis, the type IV pili of bacterial cells (Russel et al, 1997); flexuous 'nucleocapsids' of negative-stranded RNA genomes representing regular RNA-protein complexes condensed into coiled structures (Albertini et al, 2006;Arranz et al, 2012;Longhi et al, 2015;Ruigrok et al, 2011); and capsids of numerous plant viruses (Stubbs & Kendall, 2012).…”
Section: Introductionmentioning
confidence: 99%